Identification of Children with Special Needs in Inclusive Schools - Dewi Ratih Rapisa; Eviani Damastuti; Adelia Ananda Putri (Journal of ICSAR, 2021)
This study aims to analyze the types and characteristics of children with special needs, especially children who experience obstacles in the academic field. This research was motivated by various cases where there were limitations of teachers in identifying children with special needs. This research method is descriptive with the technique of collecting data from a literature review of various references that are relevant to the observed symptoms. The data collected were analyzed descriptively qualitatively so that we could recognize the types and characteristics of children with special needs, especially children who experience obstacles in the academic field. The results of the literature review reveal that children with special needs, especially children who experience obstacles in the academic field, are divided into three types, which is intellectual disability, learning disability, and slow learner.